Faktor Keterlambatan Berkas Rekam Medis Rawat Inap di RSUP Kariadi Semarang - Riza Umami Agustin; Feby Erawantini; Mochammad Choirur Roziqin (Politeknik Negeri Jember, 2020)
That delay file medical record in-patient could impede the service event assembling, medical record filling,koding, cause to be lost or damaged and probably file. medical recordThat file medical record in-patient rsup.drAre still experiencing keterlabatan. kariadi semarangBased on the observations and the interviewsconducted by researchers implementation has been delayed at pjrm. assembling orThe purpose of thisresearch is conducting apasaja analyzing the factors that cause the repayment record. in-patient medicalfileThe kind of research used the qualitative.This study using theory lawreens green variable, predisposingfactors enabling, factors reinforcing factors and the repayment of file medical record by, throughinterviews. The research results show delays in the repayment of file medical record in-patient caused byindividual competence the attitude the repayment of knowledge and the officer to file medical record , thesecond caused by of facilities and infrastructure who are supporting yet there still implementation has beendelayed return and the lack of a motivation that granted to officers .In reaction to this, should be created aroutine meeting that special committee to discuss about delays in the repayment of medical record file so thatthey do not file medical record delays there was a problem .